Chelate-free "turn-on"-type fluorescence detection of trivalent metal ions. Issue 89 (20th October 2022) - Matsumoto, Shota; Umeno, Tomohiro; Suzuki, Noriko; Usui, Kazuteru; Kawahata, Masatoshi; Karasawa, Satoru
Abstract : For the detection of trivalent ions, the chelate-free pH-responsive "Turn-ON"-type fluorescence probes based on INAs were constructed. Based on the X-ray analysis, cationic INAs formed unique outer-sphere complexes for Al III ions. Abstract : Trivalent metal ions are essential elements in materials and life sciences. To date, fluorescence is the gold standard for the detection of trivalent metal ions, which form a complex with fluorescent chelate ligands (Lewis base type). In this study, we report pH-responsive fluorescent probes for the selective detection of trivalent metal ions that utilize a new chelate-free approach using Brønsted base-type probes. Moreover, an X-ray structure of the outer-sphere aluminum(iii ) aqua complex coordinated by the fluorescent probes through hydrogen bonds was discovered. The outer-sphere complex consisting of an Al(iii ) aqua complex and protonated cationic probe showed cation-cation coordination.